2020
DOI: 10.1088/1757-899x/917/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

A Review Survey on the Use Computer Animation in Education

Abstract: The use of animation computers in today’s world is beneficial in many sectors. Animations development has changed over time and usage context, and illustrate phenomena and concepts that difficult to understand. Animations may not always be useful, however, and teachers using animations need to understand the importance of it. This paper focused on illustrating potential applications of animations in language learning and education, on identifying evidence- based principles for their design and use, and on prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Education-entertainment is a practical solution for children to improve social and emotional learning capabilities (Hubley et al, 2020), especially during a pandemic. Interactive learning resources significantly influence their learning abilities and adaptability (Islam et al, 2014), consistent with another study where computer animation enables children to visualize content or ideas difficult to visualize in the actual world and explain difficult-to-understand concepts (Rohana Mansor et al, 2020). Additionally, illustrations can depict abstract concepts and generally unseen things and phenomena through visible metaphors.…”
Section: Discussionsupporting
confidence: 73%
“…Education-entertainment is a practical solution for children to improve social and emotional learning capabilities (Hubley et al, 2020), especially during a pandemic. Interactive learning resources significantly influence their learning abilities and adaptability (Islam et al, 2014), consistent with another study where computer animation enables children to visualize content or ideas difficult to visualize in the actual world and explain difficult-to-understand concepts (Rohana Mansor et al, 2020). Additionally, illustrations can depict abstract concepts and generally unseen things and phenomena through visible metaphors.…”
Section: Discussionsupporting
confidence: 73%
“…There is also a possibility of showing static data with animation using different camera angles to help spatial understanding [ 24 ]. Mansor et al [ 25 ] have reviewed that animations are effective learning tools because of the audio, visuals, and design. They also concluded that animations are useful in helping the viewers visualize things that are not visible and are difficult to visualize without aid.…”
Section: Related Workmentioning
confidence: 99%
“…The efficiency in showing movement, spatial relationships, and model accuracy is the reason we chose continuous representations. We have also decided to test the Video and Narrated Video between each other because of the benefits stated by Mansor et al [ 25 ] and to test for audio impact. Our static representations, the Static and Abstract Illustrations, were chosen because of the benefits of illustrative techniques.…”
Section: Representations Designmentioning
confidence: 99%